The Effect of Wheat Flour Substitution with Sorghum Flour (Sorghum bicolor, L) on Consumers' Preference Levels for Cookies - Sondang Dhea Farrah; Esi Emilia; Rasita Purba; Fatma Tresno Ingtyas; Marhamah Marhamah (Media Pendidikan Gizi dan Kuliner, 2022)
Cookiesor pastries are food products made from flour as basic ingredients which are baked to have a water content of less than 5%. Usually the recipe for cookie products is enriched with fat and sugar and added developer ingredients. The use of wheat flour in Indonesia is still increasing, so by utilizing sorghum flour it will be able to help reduce the use of wheat and can help the government in food diversification programs. The main factor that is seen to assess the quality and quality of a product is based on the appearance of the product presented, the aroma, and the taste of the product. The purpose of this study was to analyze the level of consumer preference (color, taste, aroma, texture) through organoleptic tests. The design of this study used experimental research with the RAL method (Completely Randomized Design). Sorghum flour substitution formulation in 4 treatments, namely control (T0), 50% (T1), 70% (T2), 90% (T3). The research location is at Medan State University with 30 research subjects. Organoleptic test results data were analyzed descriptively using the percentage of consumer acceptance of each cookie formulation and continued with the one-way-Anova test and continued with the DMRT (Duncan) test. The results of this study indicate that the best formula is a substitution of 50 percent sorghum flour obtained from the mean values of 4.55 control formulations (T0), 4.34 (T1), 3.97 (T2), and 3.70 (T3). Organoleptic test results data were analyzed descriptively using the percentage of consumer acceptance of each cookie formulation and continued with the one-way-Anova test and continued with the DMRT (Duncan) test. The results of this study indicate that the best formula is a substitution of 50 percent sorghum flour obtained from the mean values of 4.55 control formulations (T0), 4.34 (T1), 3.97 (T2), and 3.70 (T3). Organoleptic test results data were analyzed descriptively using the percentage of consumer acceptance of each cookie formulation and continued with the one-way-Anova test and continued with the DMRT (Duncan) test. The results of this study indicate that the best formula is a substitution of 50 percent sorghum flour obtained from the mean values of 4.55 control formulations (T0), 4.34 (T1), 3.97 (T2), and 3.70 (T3).